Cardiac Monitoring to Aid in Diagnosis - Mitra, Manu (JINAV: Journal of Information and Visualization, 2020)
Cardiac Monitoring refers monitoring heart activity to determine patient’s condition relative to their cardiac rhythm. The reason of having cardiac monitoring is to determine any unusual activity of heart; so that it can diagnosed before the severity condition of patient increases. There are many ways to determine condition of health of heart. There are many others, however, in this paper flexible and comfortable ways are discussed without inconvenience for the patient. For example – flexible device on the finger, flexible skin like monitor small enough size of a bandage, and self-powered cardiac pacemaker using nanogenerator.